Flexible Organic Electronic Ion Pump for Flow‐Free Phytohormone Delivery into Vasculature of Intact Plants - Iwona Bernacka‐Wojcik; Loïc Talide; Ilaria Abdel Aziz; Jan Simura; Vasileios K. Oikonomou; Stefano Rossi; Mohsen Mohammadi; Abdul Manan Dar; Maria Seitanidou; Magnus Berggren; Daniel T. Simon; Klas Tybrandt; et al. (Advanced Science, 2023)
Abstract Plant vasculature transports molecules that play a crucial role in plant signaling including systemic responses and acclimation to diverse environmental conditions. Targeted controlled delivery of molecules to the vascular tissue can be a biomimetic way to induce long distance responses, providing a new tool for the fundamental studies and engineering of stress‐tolerant plants. Here, a flexible organic electronic ion pump, an electrophoretic delivery device, for controlled delivery of phytohormones directly in plant vascular tissue is developed. The c‐OEIP is based on polyimide‐coated glass capillaries that significantly enhance the mechanical robustness of these microscale devices while being minimally disruptive for the plant. The polyelectrolyte channel is based on low‐cost and commercially available precursors that can be photocured with blue light, establishing much cheaper and safer system than the state‐of‐the‐art. To trigger OEIP‐induced plant response, the phytohormone abscisic acid (ABA) in the petiole of intact Arabidopsis plants is delivered. ABA is one of the main phytohormones involved in plant stress responses and induces stomata closure under drought conditions to reduce water loss and prevent wilting. The OEIP‐mediated ABA delivery triggered fast and long‐lasting stomata closure far away from the delivery point demonstrating systemic vascular transport of the delivered ABA, verified delivering deuterium‐labeled ABA.